2018
DOI: 10.1097/md.0000000000011511
|View full text |Cite
|
Sign up to set email alerts
|

Pentalogy of Cantrell associated with unilateral anophthalmia

Abstract: Rationale:Pentalogy of Cantrell, a very rare congenital condition, has an estimated incidence of 5.5 per 1 million live births. It includes five defects: a midline supraumbilical wall defect, a diaphragmatic defect, a cleft distal sternum, a defect in the diaphragmatic pericardium, and an intracardiac defect. Very few cases of this condition have been reported in the literature, most of them diagnosed in the second or third trimester of pregnancy.Patient concerns:We present a case of pentalogy of Cantrell asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
5
11
0
1
Order By: Relevance
“…The only variable that basically represents, without a doubt, the most significant risk factor for pterygium is the exposure to UV radiation [13,18,19,29,40]. This is also confirmed by our study, both as a variable whose status was declared by every patient, as well as a potential consequence of the residence context and outdoor activities involved by this reason [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Resultssupporting
confidence: 72%
“…The only variable that basically represents, without a doubt, the most significant risk factor for pterygium is the exposure to UV radiation [13,18,19,29,40]. This is also confirmed by our study, both as a variable whose status was declared by every patient, as well as a potential consequence of the residence context and outdoor activities involved by this reason [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55].…”
Section: Resultssupporting
confidence: 72%
“…Instead, they were detected during Nance's analysis, making this method less reliable [17]. The current study showed a higher degree of reproducibility of the digital caliper method compared to the wire method following the three steps of resuming the measurements as confirmed by other studies, too [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Random Errorsupporting
confidence: 66%
“…The physico-chemical theory of inflammation also has an important shortcoming in that it attempts to reduce the inflammatory process to the laws of physical chemistry and colloidal chemistry [34][35][36]. Such an approach to the problem ignores the biological essence of the inflammatory reaction, and therefore has a mechanistic character [37].…”
Section: Developing Physical Chemistry and Biological Chemistry In Thmentioning
confidence: 99%